Aloe vera stimulate cell proliferation, cell migration, expression of vascular endothelial growth factor-A (VEGF-A), and c-Jun N-terminal kinase-1 (JNK-1) on fibroblast of diabetic rat models - Firdaus, Insanul; Arfian, Nur; Wahyuningsih, Mae Sri Hartati; Agustiningsih, Denny (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
The disturbance of cell migration and cell proliferation,diminished production of vascular endothelial growth factor-A (VEGF-A) and c-Jun N-terminal kinase-1 (JNK-1) are important factors in wound healing process. Aloe vera contains active compounds which can help in the wound healing process. Thestudy aimed to investigate the effect of ethanol extract ofA. veraon cell proliferation, cell migration, VEGF-A and JNK-1 expression of skin fibroblast cells of diabetic rats. The primary skin fibroblast cells were isolated from diabetic Wistar rat and incubated with the A. vera extract in various concentrations i.e. 500 (AV500), 250 (AV250), and 125 µg/Ml (AV125) for 24, 48 and 72 h.The cell proliferation was examined visually by counting the cells number, the cell migration was observed using in vitro scratch assay, whereas VEGF-A and JNK-1 expression were examined using RT-PCR. In 24 and 48h incubation,the cell proliferation of AV500 and AV250 groups had higher number of cells than negative control group,but there was no significant difference (p>0.05). However in72 h incubation,the cell proliferation of AV500 group (29.33±1.28x104 cells/mL)was significantly different compared to negative control group (22.91±3.21x104 cells/mL) (p<0.05). In 24 h incubation, the cell migration of AV500(78.13±7.18%), AV250 (73.88±4.75%) and AV125 (68.80±17.11%) groupswere significantly higher thanthat of negative control group (53.91±2.74%) (p<0.05). In contrastin 48 and 72 hincubation,there were no significantly different in cell migration (p>0.05).The expression of VEGF-A and JNK-1 after incubation with the AV500 for 48 h, weresignificantly higher than those of negative control group (p<0.05).In conclusion, A. vera increases cell proliferation, cell migration, VEGF-A and JNK-1 expression offibroblast cellof diabetic rat skin.